Posttraumatic stress disorder neurophysiology and clinical correlates in pediatric critical care: conceptualizing a PICU-PTSD framework - Hay, Rebecca E. (Frontiers in Pediatrics, 2025)
Posttraumatic stress disorder (PTSD) is common in child and parent survivors of critical illness, with significant negative impact on life after survival. Understanding the neuroscience and pathophysiology of contributing factors to PTSD within the pediatric intensive care unit (PICU) context can help identify potentially modifiable risk factors, aid risk stratification, and identify knowledge gaps for further study. This narrative review explores the evidence-based neurophysiology of PICU-PTSD, summarizing predisposing and protective factors related to critical care and conceptualizing the disorder in a biopsychosocial framework.